Crime of privilege [compact disc, unabridged] : a novel - Walker, Walter (Random House Audio, 2013)
George Becket, assistant to the Cape & Islands District Attorney, makes a fateful decision when he agrees to re-open a scandalous case: the unsolved murder of a young woman. The investigation puts him up against not only one of America's most powerful and adored families, but also the most haunting mistake of his own past. Intelligent and engrossing, a thriller about class and crime, a novel about the ways in which power and privilege corrupt justice.